Frequency-dependent dielectric contribution of flexoelectricity allowing control of state switching in helicoidal liquid crystals. - Outram, B; Elston, S (2013)
The contribution of flexoelectric polarization to the dielectric susceptibility in helicoidal liquid crystals is formulated for the static equilibrium case, and further in the case of a time-varying field. A dispersion of the dielectric permittivity due to the frequency response of flexoelectric switching is described. The special case of a negative dielectric-anisotropy nematic material is considered and experimentally shown to agree with the analytical theory. It is further demonstrated how relaxation of the flexoelectric contribution to the dielectric tensor in this special case can be exploited to switch between states in cholesteric liquid crystal structures by altering the applied time-dependent field amplitude, if Δε<0 and (e(1)-e(3))(2)/(K(1)+K(3))>-Δεε(0). Consequentially, a versatile mechanism for driving between states in liquid crystal systems has been demonstrated and its implications for technology are suggested, and include dual-mode, bistable, and transflective displays.